2019
DOI: 10.1021/acs.jafc.8b05141
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Human-Health Impacts of Mycotoxins in Somalia

Abstract: Mycotoxins are secondary metabolites produced by various molds that contaminate many staple foods and cause a broad range of detrimental health effects in animals and humans through chronic exposure or acute toxicity. As such, the worldwide contamination of food and feed with mycotoxins is a significant problem, especially in sub-Saharan Africa. In this study, mycotoxin occurrence in staple foods consumed in Somalia was determined. A total of 140 samples (42 maize, 40 sorghum, and 58 wheat) were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…The mycotoxins included AF, FUM, CIT, NIV, OTA, STER, ZEN and the emerging Fusarium mycotoxins BEAU and MON. A similar diversity of mycotoxins and other metabolites was previously reported in cowpea [ 19 ], maize [ 8 , 13 , 15 ], peanut [ 14 ] and rice [ 20 ] in Nigeria and elsewhere in sub-Saharan Africa [ 21 , 22 , 23 , 24 , 25 , 26 ], emphasizing that mycotoxin contamination of foods is an important food safety challenge that is yet to be solved in sub-Saharan Africa. To date, however, only few mycotoxins including AFs, FUM, OTA and ZEN determined by ELISA or thin-layer chromatography were reported in sorghum and millet in Nigeria [ 17 , 27 ].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The mycotoxins included AF, FUM, CIT, NIV, OTA, STER, ZEN and the emerging Fusarium mycotoxins BEAU and MON. A similar diversity of mycotoxins and other metabolites was previously reported in cowpea [ 19 ], maize [ 8 , 13 , 15 ], peanut [ 14 ] and rice [ 20 ] in Nigeria and elsewhere in sub-Saharan Africa [ 21 , 22 , 23 , 24 , 25 , 26 ], emphasizing that mycotoxin contamination of foods is an important food safety challenge that is yet to be solved in sub-Saharan Africa. To date, however, only few mycotoxins including AFs, FUM, OTA and ZEN determined by ELISA or thin-layer chromatography were reported in sorghum and millet in Nigeria [ 17 , 27 ].…”
Section: Resultssupporting
confidence: 70%
“…With respect to food type, as much as 8–98 times higher average PDIs of the population categories (children, adolescents and adults) were calculated for consumers of aflatoxin-contaminated peanut than for the consumers of other foods ( Table 5 ). The exposure levels to total AF estimated in the present study for peanut consumers was as much as six times higher than the levels reported in a nationwide study in Nigeria (187–1124 ng/kg bw/day) [ 14 ], whereas the exposure levels for maize consumers were similar to the values obtained in Ondo state, Nigeria (138–830 ng/kg bw/day) [ 58 ] but lower than previous reports from a nationwide study in Nigeria (318–1909 ng/kg bw/day) [ 57 ] and in Somalia (649–1614 ng/kg bw/day) [ 26 ]. Consequent to the estimated high exposures, the MOEs were far lower than 10,000, with the values for peanut consumers being the lowest (0.026–0.16) compared to other foods: maize (0.20–1.23), rice (0.41–2.50) and sorghum (2.51–15.3).…”
Section: Resultssupporting
confidence: 70%
“…In animals, FB1 produces equine leucoencephalomalacia, porcine pulmonary edema, and rodent hepatic cancer among other toxic effects [6,7]. Consumption of F. verticillioides contaminated corn has been correlated with an increased incidence of human esophageal cancer in Southern Africa and China [8][9][10][11][12][13][14]. Three molecular targets of the FB1 have been described in plants so far: Ceramide synthase (CS) [15], low pHi α-amylase isoforms [5], and the PM H + -ATPase [16].…”
Section: Introductionmentioning
confidence: 99%
“…J Food Sci Nutr The 7(1): 001-010. DOI: https://dx.doi.org/10.17352/jfsnt.000026 economic consequences as well as severe health effects to humans and animals as a result of acute toxicity or chronic exposure [5,17,80]. The health consequences resulting from exposures to mycotoxins in humans range from acute to chronic effects such as afl atoxicosis, organ toxicity, neurotoxicity, Mutagenicity, Carcinogenicity, cytotoxicity, Growth retardation, diarrhea and vomiting, Immunosuppression, reproductive disorders, and death [4,17,27,35,42,43,52].…”
Section: Health and Economic Impact Of Mycotoxinsmentioning
confidence: 99%